Pembuatan Karbon Aktif Magnetik Dari Kulit Singkong Untuk Menurunkan Kadar Logam Fe Dalam Air - Lamuru, Afrianti S; Mahirullah, Mahirullah; Alimin, Jumriani; Hambali, A. Miftah Alya Patrisia (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Groundwater often contains iron (Fe), which can cause a metallic taste, yellow color, iron bacteria growth, and turbidity. One method used to reduce iron content in water is the use of activated carbon. However, activated carbon has disadvantages such as long separation times and requires filtration equipment that can filter activated carbon. This study aims to produce magnetic activated carbon from cassava peel composite with magnetite to be used in reducing iron concentration in water. The methods used in this study included carbonization, activation with 2.5% KOH activator, activated carbon and magnetite composite with a 2:1 ratio, FTIR analysis, quality analysis through water content, ash, and iodine adsorption capacity tests in accordance with SNI 06-3730-1995 standards, surface area analysis using a BET instrument, and Fe adsorption application with varying times. The results showed that magnetite activated carbon was successfully synthesized, as confirmed by FTIR analysis, which indicated the presence of Fe-O bonds in the activated carbon and its ability to be attracted to a magnetic field. The adsorption effectiveness of magnetic activated carbon reached 77.38% with a contact time of 30 minutes. The quality test results of magnetic activated carbon did not meet the SNI 06-3730-1995 standard, with an iodine adsorption capacity of 620 mg/g. This study provides an overview of magnetic activated carbon composites  from cassava peel, which have advantages in the separation process between adsorbent and adsorbate after adsorption. Research on the optimization of the manufacturing process for magnetic activated carbon that meets SNI standards is urgently needed.